An investigation into some of the problems affecting the teaching and learning of biochemistry in Transkei Colleges of Education - Qokweni, Patiswa (Rhodes University, Faculty of Education, Department of Education, 1990)
The study investigated some of the problems experienced in the teaching and learning of biochemistry - a section in the Senior Certificate biology syllabus - in the Transkei Colleges of Education. Biochemistry is often labelled a difficult area, therefore, the study was an attempt to identify the problems encountered by biology teachers and lecturers in teaching biochemistry and by student-teachers in learning it. Questionnaires were admlninistered to final-year biology major student-teachers in the colleges, and to the biology teachers and college lecturers. Examiners and subject advisers for biology were interviewed. The questionnaires required the respondents to identify the following: 1. Areas of biochemistry they find difficult. 2. Areas of biochemistry they find easy to understand. 3. Possible reasons for the students' poor performance in biochemistry. 4. Possible suggestions for improvement. The student-teachers were further given a concept test to test their understanding of the concept 'photosynthesis'. After analysing the data, the findings were used to make some recommendations, in an attempt to improve the teaching of biochemistry by the teachers and lecturers and of the learning of biochemistry by the students
Keywords: Biochemistry -- Study and teaching -- South Africa -- Transkei